Rebecca story collection - Greene, Jacqueline Dembar; Hunt, Robert, 1952- (Middleton, WI : American Girl Pub., 2009)
"Rebecca Rubin dreams of being an actress. Growing up in a big Jewish family, Rebecca has never been outside her immigrant neighborhood in New York City. As her world expands and she sees the plight of new immigrants, Rebecca decides that acting means not just performing, but also taking a stand against injustice"--P. [4] of cover.
New January 2013.
Keywords: Jews -- New York (State) -- New York -- Juvenile fiction; Families -- New York (State) -- New York -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction